2013
DOI: 10.1007/s00246-013-0766-5
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Congenital Heart Disease and Outcomes After Surgical Repair Among Children With Turner Syndrome: A Single-Center Review

Abstract: Turner syndrome (TS), a genetic abnormality affecting 1 in 2,500 people, is commonly associated with congenital heart disease (CHD). However, the surgical outcomes for TS patients have not been well described. This study reviewed the spectrum of CHD in TS at the authors' center. The authors report outcomes after coarctation of the aorta (CoA) repair or staged palliation of hypoplastic left heart syndrome (HLHS) and then compare the surgical outcomes with those of non-TS patients undergoing like repair. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 20 publications
1
55
1
2
Order By: Relevance
“…Only lesions with an estimated prevalence above 1% are listed. Few studies have looked into the prevalence of hypoplastic left heart syndrome (or Shone complex) in TS; one study reported hypoplastic left heart syndrome in 3.5% of 173 consecutive girls with TS12 and the estimated prevalence of TS in hypoplastic left heart syndrome ranges from 1% to 7% 11…”
Section: Introductionmentioning
confidence: 99%
“…Only lesions with an estimated prevalence above 1% are listed. Few studies have looked into the prevalence of hypoplastic left heart syndrome (or Shone complex) in TS; one study reported hypoplastic left heart syndrome in 3.5% of 173 consecutive girls with TS12 and the estimated prevalence of TS in hypoplastic left heart syndrome ranges from 1% to 7% 11…”
Section: Introductionmentioning
confidence: 99%
“…In children with HLHS it has been described that 5–12% of cases are associated with chromosomal or syndromic abnormalities, including Turner syndrome (monosomy X), 22q11.2 microdeletion syndrome and Jacobsen syndrome (11q deletion). Providing information about the association of CHDs with these syndromes is important when counselling future parents, given the influence of genetic conditions on surgical success and long‐term outcome . Most syndromes are detectable after birth and/or display multiple malformations.…”
Section: Introductionmentioning
confidence: 99%
“…In a cohort of 24 patients, only one required reintervention in the first 30 days after surgery. During an 8.8 years follow‐up, none had significant aortic dilatation, rupture or aneurysm dissection . No deaths were reported …”
Section: Discussionmentioning
confidence: 96%
“…Zanjani et al demonstrated that the risk of AWI and mortality were higher after surgery. Nevertheless, Cramer et al reported more favorable outcomes. In a cohort of 24 patients, only one required reintervention in the first 30 days after surgery.…”
Section: Discussionmentioning
confidence: 99%